2014
DOI: 10.1007/s00224-014-9543-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural Tractability of Counting of Solutions to Conjunctive Queries

Abstract: In this paper we explore the problem of counting solutions to conjunctive queries. We consider a parameter called the quantified star size of a formula ϕ which measures how the free variables are spread in ϕ. We show that for conjunctive queries that admit nice decomposition properties (such as being of bounded treewidth or generalized hypertree width) bounded quantified star size exactly characterizes the classes of queries for which counting the number of solutions is tractable. This also allows us to fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 33 publications
(113 reference statements)
2
58
0
Order By: Relevance
“…Define contractpA, Sq to be the graph on vertices S obtained by starting from GrSs and adding an edge between any two vertices that appear together in an D-component of pA, Sq. 3 Example 4.1: Let φpu 1 , u 2 , u 3 , u 4 q be the pp-formula…”
Section: A Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Define contractpA, Sq to be the graph on vertices S obtained by starting from GrSs and adding an edge between any two vertices that appear together in an D-component of pA, Sq. 3 Example 4.1: Let φpu 1 , u 2 , u 3 , u 4 q be the pp-formula…”
Section: A Statementsmentioning
confidence: 99%
“…Previous work showed that, for bounded arity Φ, countpΦq is fixed-parameter tractable if Φ satisfies the tractability condition; interreducible with the parameterized clique problem if Φ satisfies the contraction condition but not the tractability condition; and as hard as the parameterized counting clique problem otherwise (see [4] for a precise statement). 3 Note that in previous articles [4], [18] this graph was defined in terms of the core of the given formula.…”
Section: A Statementsmentioning
confidence: 99%
“…For instance it is known that the boolean case is tractable for CQ having bounded width for various notions of width. In order to capture also non boolean queries the notion of quantified-star size was extended for various notions of width [13]. Based on this definition for hypertreewidth, the result reads as follows: Theorem 8.…”
Section: Counting the Number Of Solutionsmentioning
confidence: 99%
“…Another direction is to study the complexity of counting answers to formulas; in this problem, one is given a first-order formula and a finite structure, and the goal is to count the number of assignments, to the free variables of the formula, that satisfy the formula on the structure. There have been recent results on this direction in the context of primitive positive formulas [28,23] and existential positive formulas [24].…”
Section: Resultsmentioning
confidence: 99%